A study of the impact of business education on global career mobility: An analysis of location and international orientation. Issue 1 (2nd May 2017) - Silvanto, Sari; Ryan, Jason; Gupta, Vipin
Abstract : Purpose: This paper aims to develop a clearer understanding of the role of business education and business schools in fostering global mobility. As business schools seek to educate managers who can work globally and adjust to new business and cultural environments, it is important to assess which specific dimensions of business education, such as the location of the school and its curriculum, play a significant role in fostering greater global mobility among business graduates. This also helps how business schools potentially influence global talent flows. Design/methodology/approach: This study uses an empirical research methodology in the form of a multivariate analysis to examine a sample of 91 business schools that are accredited by Association to Advance Collegiate Schools of Business (AACSB) in the 2015 Financial Times Global MBA Ranking . Findings: This study finds that international mobility of MBA graduates is mediated both by the design of the curriculum and the location of the business school. MBA graduates from leading business schools that offer greater levels of international experiential learning are more likely to pursue overseas careers after graduation. MBA graduates from leading business schools that are located in economically globalized locations, by contrast, are often more likely to remain in the country where they studied after graduation to pursue local employment opportunities. Originality/value: This paper contributes to the knowledge of how business education influences the international mobility of business graduates and how it influences global talent flows.